PENGARUH ASET PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN DAN PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA: MANAJEMEN LABA - Rista Handayani; Siti Asmonah (Yayasan Kayyis Mulia Jaya, 2025)
This study aims to 1). Determine and analyze the effect of deferred tax assets on earnings management, 2). Determine and analyze the effect of deferred tax expenses on earnings management, 3). Determine and analyze the effect of tax planning on earnings management, and 4). Determine and analyze the effect of deferred tax assets, deferred tax expenses, and tax planning on earnings management. This research was conducted by analyzing the annual financial statements of companies in the energy sector listed on the Indonesia Stock Exchange during the period from 2020 to 2024. The sampling technique used in this study is purposive sampling, resulting in a total sample of 20 companies in the energy sector for the 2020–2024 period, with a total of 100 research data. The research method used is descriptive research with a quantitative approach, utilizing secondary data in the form of annual financial reports from each company selected as a sample. The independent variables used in this study are Deferred Tax Assets (X1), Deferred Tax Expenses (X2), and Tax Planning (X3), while the dependent variable is Earnings Management (Y). To test and analyze the data, this study used the panel data regression method. The data analysis was carried out using the EViews 13 software. The results of this study indicate that Deferred Tax Assets partially affect Earnings Management, as shown by the t-statistic value > t-table (3.683774 > 1.66105). Deferred Tax Expenses do not partially affect Earnings Management, with a t-statistic value < t-table (0.295259 < 1.66105). Tax Planning also does not partially affect Earnings Management, with a t-statistic value < t-table (-0.294034 < 1.66105). However, simultaneously, Deferred Tax Assets, Deferred Tax Expenses, and Tax Planning have a significant effect on Earnings Management, as indicated by the F-statistic value > F-table (4.654637 > 2.70). Keywords: Deferred Tax Assets; Deferred Tax Expenses; Tax Planning; Earnings Management.